THE EFFECT OF PROBLEM SOLVING-BASED PAI LEARNING ON STUDENTS' CRITICAL THINKING SKILLS - Safitri, Hany; Nawangsari , Dyah; Mustajab, Mustajab (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the effect of problem solving-based Islamic Religious Education (PAI) learning on students' critical thinking skills. This research method uses a quantitative approach with a pseudo-experimental design. The research sample consisted of 60 students divided into control and experimental groups. Data were obtained through critical thinking skills test and analyzed using t-test. The results showed that problem solving-based learning significantly improved students' critical thinking skills compared to conventional learning. The implication of this study emphasizes the importance of implementing innovative learning strategies in PAI curriculum to develop 21st century skills in students.